Offenes Foramen ovale: gute Gründe, es zu verschließen - Meier, Bernhard (DMW - Deutsche Medizinische Wochenschrift, 2018)
A patent foramen ovale (PFO) is not to be considered a disease as it is present in about 25 % of people. Yet, it is the prime reason for paradoxical embolism that can cause serious problems, such as death, stroke, myocardial infarction, and peripheral ischemia. The frequency of such events is probably underestimated as other causes tend to be blamed for them. Device PFO closure can be easily accomplished as outpatient procedure with minimal discomfort and risk and it has been referred to as mechanical vaccination. Randomized trials have proved its value for reduction of recurrent stroke. There is also good evidence that PFO closure solves problems like platypnoea orthodeoxia and exercise desaturation, improves migraine, and is helpful in sleep apnoea. In addition, it renders diving and high altitude climbing safer. The absolute risk of a PFO is dependent on its size and its association with an atrial septal aneurysm, a Eustachian valve, or a Chiari network. The number needed to treat to prevent one stroke by PFO closure may be as low as 2 over lifetime in selected patients.
Keywords: Foramen ovale; Herzinfarkt; Hirnschlag; Schirmverschluss